Comparing performance on a simulated 12 hour shift rotation in young and older subjects. Issue 1 (1st January 2001) - Reid, K; Dawson, D
Abstract : OBJECTIVES: To simulate a 12 hour shift rotation and measure the difference in performance if any, between older and younger subjects. Significant reductions in neurobehavioural performance during shift work and particularly night work have long been recognised. There are conflicting reports of the effects of 12 hour shifts on performance, alertness, and safety. Furthermore, research suggests that older shift workers have more sleep disruption and maladaption to shift work. When this is combined with longer hours at work there may be considerable reductions in performance for older compared with younger workers. METHODS: Thirty two subjects were allocated to groups according to age. Group one had 16 subjects with a mean (SD) age of 21.2 (2.7) years, and group two had 16 subjects with a mean (SD) age of 43.9 (6.8) years. Subjects came to the laboratory for six consecutive days and completed a simulated 12 hour shift rotation consisting of two 12 hour day shifts (0700–1900), followed by two 12 hour night shifts (1900–0700). During the work period subjects completed a computer administered neurobehavioural performance task every hour. RESULTS: Performance for the older subjects was consistently lower than for the younger subjects. There was a significant difference in performance across the shift between older and younger subjects. There was a significant change in performance across the shifts in the older subjects, such that performance significantly increased across the day shifts and decreased across the night shifts. By contrast, the younger subjects were able to maintain performance across both day shifts and the second night shift. CONCLUSIONS: There are significant differences in performance of older and younger subjects during a simulated 12 hour shift rotation. Future studies both in the field and the laboratory would be useful in determining whether this is typical and if there are any important consequences for the older worker on 12 hour shifts.